Good Governance Implementation in Transimuda Arts Group in the Transmigrant Community Areas - Putri Dyah Indriyani; Tutung Nurdiyana (LEGAL BRIEF, 2022)
The principles of good governance need to be applied in all lines of the life of the Indonesian people. This fosters and applies the main foundation and the character of society to become stronger, especially in art groups that develop in society. The transmigrant community has characteristics that are acculturated into the new culture. The aim of this research is to analyze the implementation of the principles of good governance in the Transimuda arts group in the transmigrant community. The concept used is good governance according to the United Nations Development Program (UNDP) which is the analytical tool in this study. Through data collection techniques in the form of observation, interviews, and documentation it was concluded that the implementation of good governance in the Transimuda art group in the transmigrant community received maximum appreciation from several stakeholders which made the art group more well-known and varied in its development.